Constitutional legal support of the unity, stability and coherence of Russian legal system - S. Ivanov (Правоприменение, 2018)
The subject. The paper is devoted to the issues of the system of constitutional legal guarantees of unity, stability and consistency of the Russian legal system, the problems of their effective implementation.The purpose of the paper is to reveal the actual problems of constitutional legal support of the unity, stability and coherence of the Russian legal system.The methodology of the study includes general scientific methods (analysis, synthesis, comparative method, description) as well as particular academic methods (formal-legal method, interpretation of legal acts).Results, scope of application. It is revealed that the constitutional legal support of unity, stability and consistency of the Russian legal system occurs by means of action of two types of special constitutional legal guarantees: conflict and competence ones. A number of problems of effective support of the unity, stability and consistency of the domestic legal system are identified. The problems include gaps and other defects of constitutional regulation, the lack of a legal mechanism to ensure the supremacy of the foundations of the constitutional system and others.Conclusions. There is a number of amendments to the existing constitutional legislation proposed to solve the identified problems.